Seasonal Variations in Physico-Chemical Properties and Biodiversity in Betana Pond, Eastern Nepal - Niroula, B.; Singh, K.L.B.; Thapa, G.B.; Pal, J. (Our Nature, 2011)
A total of 62 species of aquatic macrophytes belonging to 33 families (Alga 1, Bryophyte 1, Pteridophytes 5, Angiospermic dicots 25 and monocots 31) and 38 species of aquatic macro-fauna (Birds 17, Reptiles 3, Amphibians 3, Fishes 12, Molluscs 1 and Arthropods 2) were recorded from Betana pond, eastern Nepal. Physico-chemical parameters of the pond water displayed different characteristics with seasons. More seasonal fluctuations in turbidity (0.76-26.01 NTU), carbon dioxide (4.58-73.92 mg/l) and chloride content (2.0-7.0 mg/l) were recorded in the pond. DOI: 10.3126/on.v8i1.4330